Effects of microbial transglutaminase on textural, water distribution, and microstructure of frozen‐stored longtail southern cod (Patagonotothen ramsayi) fish mince gel. Issue 6 (23rd January 2022) - Zhang, Nana; Yang, Ning; Yu, Wanying; Jin, Zheng; Jiang, Pengfei; Yu, Chenxu; Dong, Xiuping
Abstract: Frozen‐stored fish mince tend to have poor gelling ability due to significant myosin denaturation caused by freezing. In this study, microbial transglutaminase (MTGase) was used to improve the quality of fish mince gel products made from frozen‐stored longtail southern cod (LSC). The gel strength of the gel product increased with the addition of MTGase and reached a plateau value of ~19 N mm beyond 300 U/kg of MTGase, at the same condition, T 22 was reduced from 57.22 to 49.77 ms, T 23 was reduced from 1, 273.88 to 1, 072.27 ms. As the MTGase addition increased from 0 to 400 U/kg, the hardness of the fish surimi gel increased from 14.52 to 21.36 N, and the microstructure changed from loose to dense, respectively. This study showed that MTGase could promote gelation to improve the quality of frozen‐stored LSC fish mince gel, especially at 300 U/kg, which potentially can be utilized to produce good surimi gel products out of frozen‐stored fish. Abstract :